Project Report on Analysis and Design of Hostel Building Using Staad Pro - GIREESH P L, PRADEEPA K L, KOMAL Y and MUNIREDDY (2012)
INTERNAL GUIDE: RAVIKANT TALLURI, MVJCE
Keywords: Analysis and Design of Hostel Building Using Staad Pro